2013
DOI: 10.2147/opth.s53822
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical outcomes in patients with dry eye disease using lubricant eye drops containing polyethylene glycol or carboxymethylcellulose

Abstract: BackgroundThe purpose of this study was to compare changes in corneal staining in patients with dry eye after 6 weeks of treatment with Systane® Gel Drops or Refresh Liquigel® lubricant eye drops.MethodsPatients aged ≥18 years with a sodium fluorescein corneal staining sum score of ≥3 in either eye and best-corrected visual acuity of 0.6 logarithm of the minimum angle of resolution or better in each eye who were using a lubricant eye gel or ointment for dry eye were included in this randomized, parallel-group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 19 publications
3
40
0
3
Order By: Relevance
“…This improvement in Schirmer's test and TBUT test values is comparable to previous studies. 14,16,18,19 Improvement in OSDI score during the study period is comparable to previous studies. 6,16,20 At 12 weeks, comparison was done between Group I and Group II.…”
Section: -11supporting
confidence: 83%
See 1 more Smart Citation
“…This improvement in Schirmer's test and TBUT test values is comparable to previous studies. 14,16,18,19 Improvement in OSDI score during the study period is comparable to previous studies. 6,16,20 At 12 weeks, comparison was done between Group I and Group II.…”
Section: -11supporting
confidence: 83%
“…These adverse effects were comparable to those reported in previous clinical studies. [14][15][16][17][18] …”
Section: -11mentioning
confidence: 99%
“…The oil-like PEG400 may have provided additional benefits to improve injectability of hydrogel in the printing process. [32] When sonicated silk gel (no PEG) at the same concentration was used in the same printing process, the needle became blocked, confirming the important role of PEG400 in making silk hydrogel highly printable. Interesting, a recently published paper reported that the presence of PEG segments on silk ionomer surfaces (silk-poly-l-lysine-PEG or silk-poly-l-glutamic acid-PEG) increased the friction coefficient of the surface when compared to the control surface in the absence of PEG, likely due to the interactions of the overlapped swollen and loopy PEG segments and shearing of asperities of PEG-modified surfaces that increased adhesive forces and shear strength.…”
Section: Hmsc Proliferation In 3d Printed Constructsmentioning
confidence: 90%
“…Neck pain can also arise from chronic instillation of eye drops in a wrong position; yet chronic eye drop administration can be necessary for some eye diseases frequently seen in the course of rheumatic diseases. 30 Therefore, this problem is not only associated with primary eye diseases, but can also be related to rheumatic diseases. These patients should be instructed by clinicians about the correct position of the neck, such as avoiding the hyperextension position while instilling eye drops.…”
Section: Discussionmentioning
confidence: 99%